SPATIAL ANALYSIS OF RAINFALL AND RICE PRODUCTION OVER JAVA ISLAND CORRELATION WITH ENSO AND IOD - PRICILIA (NIM : 12811029), NADINE
Indonesia's position which is between two oceans causes it's climate to be influenced by ENSO and IOD. One of the most important climate variable in Indonesia is rainfall. Rainfall has a high variation in space and time, and also influences important sectors, such as agriculture. Information about rainfall variation becomes vital on this sector. Java Island as central of rice production in Indonesia takes a significant role in keeping national food security. Rainfall variability over Java Island has impact on food security, so effective adaptation towards climate phenomenon that influences it is necessary. This research uses lagged partial correlation method to study the relationship between ENSO-IOD, rainfall, and agriculture over Java Island for December 1991 - November 2011 period. With this method can be described the relationship between the three of them at different times. The values of correlation represent certain regions, so the spatial variation can be known. The values of correlation show that there is a stronger relationship between rainfall over Java Island and ENSO, in comparison to IOD. Strongest correlation occurs between September-October-November rainfall and June-July-August Nino 3.4 SST before. Rainfall has a strong relationship with area harvested and rice productivity. ENSO and IOD affect these two indicators, especially in Central Java, DIY, and East Java.